Targeted intervention of tumor microenvironment with HDAC inhibitors and their combination therapy strategies - Wanli Zhang; Luqi Ge; Yiwen Zhang; Zhentao Zhang; Wen Zhang; Feifeng Song; Ping Huang; Tong Xu (European Journal of Medical Research, 2025)
Abstract Histone deacetylation represents a significant epigenetic mechanism that involves the removal of acetyl groups from histones, subsequently influencing gene transcription. Overexpression of histone deacetylases (HDACs) is prevalent across various cancer types, positioning HDAC inhibitors as broadly applicable therapeutic agents. These inhibitors are known to enhance tumor immune antigenicity, potentially slowing tumor progression. Furthermore, the tumor microenvironment, which is intricately linked to cancer development, acts as a mediator in the proliferation of numerous cancers and presents a viable target for oncological therapies. This paper primarily explores how HDAC inhibitors can regulate cancer progression via the tumor microenvironment and suppress tumor growth through multiple pathways, in addition to examining the synergistic effects of combined drug therapies involving HDAC inhibitors.